Improved determination of arsenic in environmental and geological specimens using HG-AFS - Chen, Bin; Krachler, Michael; González Acevedo, Zayre I.; Shotyk, William (Journal of analytical atomic spectrometry, 2005)
A sensitive and robust analytical procedure for the determination of arsenic in plant, coal, and sediment samples using hydride generation-atomic fluorescence spectrometry (HG-AFS) has been developed. The optimised concentrations of NaBH4 and HCl required for arsine generation were 1% (m/v) and 4.5 M, respectively. Seven certified plant reference materials (CTA-OTL-1 Oriental Tobacco Leaves, CTA-VTL-2 Virginia Tobacco Leaves, GBW 07602 Bush Branches and Leaves, NIST 1547 Peach Leaves, NIST 1573a Tomato Leaves, NIST 1575 Pine Needles and NIST 1515 Apple Leaves), two certified coal reference materials (NIST 1632c Bituminous Coal and NIST 1635 Subbituminous Coal), and one marine sediment reference material (GBW 07316 Marine Sediment) were analysed for quality control purposes. Sample digestion was carried out on 200 mg sample aliquots with 3 ml HNO3 and 0.1 ml HBF4, heated in a microwave autoclave up to a temperature of 240 °C. After digestion, no evaporation of HNO3 to remove acid from the digests is needed before arsine generation can be carried out. External standard solutions were matched for the HNO3 concentration in the analyte solutions (0.042 M HNO3). Potassium iodide was found to be the ideal reagent for the quantitative reduction of As(V) to As(III), in contrast to L-cysteine. The detection limit (3σ) for As(III) was 6 ng l−1, which is 1-2 orders of magnitude lower than that reported recently by other authors using HG-AFS. This sensitive, robust and low-cost analytical procedure will be applied to the determination of As in sediment samples to help understand the mechanisms of both natural and anthropogenic As accumulation in wetlands.